Advances in Human Factors in Training, Education, and Learning Sciences Proceedings of the AHFE 2018 International Conference on Human Factors in Training, Education, and Learning Sciences, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Nazir, Salman; Teperi, Anna-Maria; Polak-Sopińska, Aleksandra (Advances in Intelligent Systems and Computing, 2019)
This book focuses on the importance of human factors in optimizing the learning and training process. It reports on the latest research and best practices and discusses key principles of behavioral and cognitive science, which are extremely relevant to the design of instructional content and new technologies to support mobile and multimedia learning, virtual training and web-based learning, among others, as well as performance measurements, social and adaptive learning and many other types of educational technologies, with a special emphasis on those important in the corporate, higher education, and military training contexts. Based on the AHFE 2018 Conference on Human Factors in Training, Education, and Learning Sciences, held July 21-25, 2018 in Orlando, Florida, USA on July 21-25, 2018, the book offers a timely perspective on the role of human factors in education. It highlights important new ideas and will fosters new discussions on how to optimally design learning experiences.